2021
DOI: 10.1186/s12910-021-00666-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and proposed solutions in making clinical research on COVID-19 ethical: a status quo analysis across German research ethics committees

Abstract: Background In the course of the COVID-19 pandemic, the biomedical research community’s attempt to focus the attention on fighting COVID-19, led to several challenges within the field of research ethics. However, we know little about the practical relevance of these challenges for Research Ethics Committees (RECs). Methods We conducted a qualitative survey across all 52 German RECs on the challenges and potential solutions with reviewing proposals f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Several of these contributions focus exclusively on one ERC, usually associated with an academic or health care institution. The literature includes descriptions of ERC operations during the pandemic in Central America and the Dominican Republic [17], China [18], Ecuador [19], Egypt [20], Germany [21], India [2224], Iran [10], Ireland [25], Kenya [26], Kyrgyzstan [27], Latin America [28], the Netherlands [29], Pakistan [30], South Africa [31,32], Turkey [33], and the United States [3436]. Most of these studies reported results from surveys, interviews, focus groups, and documentary analysis, including review of research protocols, ERC meeting minutes, and existing SOPs.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these contributions focus exclusively on one ERC, usually associated with an academic or health care institution. The literature includes descriptions of ERC operations during the pandemic in Central America and the Dominican Republic [17], China [18], Ecuador [19], Egypt [20], Germany [21], India [2224], Iran [10], Ireland [25], Kenya [26], Kyrgyzstan [27], Latin America [28], the Netherlands [29], Pakistan [30], South Africa [31,32], Turkey [33], and the United States [3436]. Most of these studies reported results from surveys, interviews, focus groups, and documentary analysis, including review of research protocols, ERC meeting minutes, and existing SOPs.…”
Section: Discussionmentioning
confidence: 99%
“…Approving the consenting process in the intensive care unit with PPE for participation in clinical trials with new drugs was a challenge faced by the EC members participating in our investigation. This was addressed by the approval of a process that would ensure video consent from patients or consent from legally acceptable or authorized representatives whenever possible, which was similar to the findings from studies conducted in Germany 16 . Waivers for consent were given only for secondary data analysis, retrospective studies and laboratory studies where leftover samples were used following de-identification 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the primacy of human rights and dignity in these situations can be challenging. Documented ethical issues in conducting research during PHEs include preparing RECs for accelerated review of studies, for instance through the establishment of ad hoc committees [3,6,[23][24][25][26][27][28][29][30]; ensuring appropriate research designs for scientific validity, social value and fair selection of participants [31]; promoting inclusive and adequate stakeholder engagement and informed consent processes [2,[32][33][34]; dealing with the specific ethical conundrum of clinical trials and human challenge studies during emergencies [35][36][37][38][39][40][41]; supporting appropriate data collection, storage and future use, including those relating to children [33,[42][43][44][45]; and maintaining mechanisms for ethics review whether in person or virtual [40,[46][47][48][49][50][51]. However, few studies specifically consider ethics review processes, procedures and governance frameworks for epidemics and public health emergencies in Africa [52].…”
Section: Introductionmentioning
confidence: 99%